ANALISIS KENAIKAN PTKP SEBAGAI UPAYA PENINGKATAN PERTUMBUHAN WAJIB PAJAK DAN PENERIMAAN PAJAK PENGHASILAN DI KPP PRATAMA PAMEKASAN - Evi Malia; Qoyyimah Qoyyimah (Fakultas Ekonomi dan Bisnis, 2016)
This research aims to determine whether the increase in taxable income were able to increase tax revenues and tax growth in KPP Pratama Pamekasan. By using quantitative descriptive method, through data collection documentation and interviews obtained by the results of research that changes in taxable income in 2013 (PTKP increased) is not able to increase the acceptance of personal income tax, while in 2014 to 2015 (PTKP fixed) able to increase tax revenues in KPP Pratama Pamekasan. This happens when a growing number of employees / workers who have income above taxable income, the increase in taxable income increasingly not lead to a reduction of the income PPh 21 in KPP pratama Pamekasan, but it also salary increases with the increase in UMK (District Minimum Wage), due to increased salaries and increase in UMK that happens nearly every year, while the increase in taxable income only occurs every few years.As for the required growth is the increase in taxable income Personal Income able to increase the growth of individual taxpayer on KPP Pratama Pamekasan, because the growth of the taxpayer beginning in 2011-2015 are likely to continue to rise although not so significant .taxpayers growth who register on KPP Pratama Pamekasan caused by people who want to get the benefit of having a NPWP. Key Word: PTKP, Personal Growth taxpayer, the individual taxpayer Revenue, Income PPh 21